Religion in psychodynamic perspective : the contributions of Paul W. Pruyser - Pruyser, Paul W. (Oxford University Press, 1991)
At his death in 1987, Paul W. Pruyser of the Menninger Foundation was widely recognized as one of America's foremost authorities on the psychology of religion. In this volume, two leading practitioners have collected ten of Pruyser's most important essays from a variety of published sources. The essays provide an overview of the major themes in Pruyser's thought and demonstrate the continuing importance of his contribution.